Designing a novel radial basis neural structure for solving the dynamical hepatitis C virus model - Sabir, Zulqurnain; Yessengaliyev, Adilkazy; Temirzhan, Abdikhalyk; Koyunbakan, Hikmet; Bhatti, Saira; Nicolas, Rana (Nature Portfolio, 2025)
The purpose of the current investigation is to design a novel radial basis neural network for solving the dynamical hepatitis C virus model in patients with a high baseline viral load, which represents the nonlinear dynamical structure. The infection and treatment in the hepatitis C virus comprise uninfected hepatocytes, creatively infected hepatocytes, and viruses. The aim of this study is to solve the dynamical hepatitis C virus model in patients with a high baseline viral load with the optimization of the Bayesian regularization scheme. A database reference solution is achieved by the explicit Runge-Kutta in interval 0 and 1 with the step size of 0.01 by data division into training as 72%, while 14%, 14% for endorsement, and testing. Twenty numbers of neurons, a feed forward neural network, activation radial basis function, and the optimization Bayesian regularization approach have been used to solve the hepatitis C virus model. The precision of the scheme is perceived by the outcomes overlapping and the reducible absolute error values, which are found as 10-06 to 10-08. A statistical evaluation utilizing various operators and proportional approaches is carried out in order to assess the solver's efficiency.
Keywords: Hepatitis C virus; Bayesian regularization; Radial basis; Optimization; Numerical outputs